Why populist democracy promotes market liberalization - Pauline Grosjean; Claudia Senik (Institute for the Study of Labor (IZA), 2008)
Using a new set of micro evidence from an original survey of 28 transition countries, we show that democracy increases citizens' support for the market by guaranteeing income redistribution to inequality-averse agents. Our identification strategy relies on the restriction of the sample to inhabitants of open borders between formerly integrated countries, where people face the same level of market development and economic inequality, as well as the same historically inherited politico-economic culture. Democratic rights increase popular support for the market. This is true, in particular, of inequality-averse agents, provided that they trust political institutions. Our findings suggest that one solution to the recent electoral backlash of reformist parties in the former socialist block lies in a deepening of democracy.
urn:nbn:de:101:1-2008060980
Keywords: D63; 330; Democracy; income inequality; redistribution; market liberalization; trust; Demokratisierung; Marktwirtschaft; Wirtschaftsliberalismus; Verteilungspolitik; Politisches System; Demokratie; Vertrauen; Transformationsstaaten; Osteuropa